Personal Archives as Collective Memory: Fragments and Forgetting in the Post-Dictatorship Argentine Theater Archives in Córdoba (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
This paper analyzes the archiving policies of theater artists in Córdoba during the return of democracy (1983-1989). It focuses on the reasons for archiving of Graciela Albarenque, Mónica Carbone, Cheté Cavagliatto and Pancho Sarmiento. The hypothesis is that these archives were constructed out of fear and joy, reflecting both the defense of democracy and the transmission of artistic experiences. The research approaches personal archives as political and aesthetic practices. The methodology included interviews and document analysis. Here the theatrical conceptions of a generation of key artists in the configuration of contemporary theater are made explicit. The role of these archives in the preservation of collective memory and their power to address the history of Argentine theaters in the post-dictatorial context is studied.
Keywords: Argentinean theater, Contemporary theater, Post-dictatorship, Córdoba